2018
DOI: 10.24272/j.issn.2095-8137.2018.035
|View full text |Cite
|
Sign up to set email alerts
|

Female choice impacts residential male takeover in golden snub-nosed monkeys (Rhinopithecus roxellana)

Abstract: In primate species with social systems consisting of one-male breeding units (OMUs), resident male takeover represents a major challenge to individual reproductive success and mating strategies. The golden snub-nosed monkey (Rhinopithecus roxellana) is characterized by large multilevel societies (MLS) comprised of several OMUs and all-male units (AMUs); however, the factors and mechanisms associated with resident male takeover, which offer important insight into primate reproduction and social strategies, are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…The R. roxellana social structure thus provides adult females with opportunities to exhibit mate choice between their own OMU male and the other adult males within the breeding band, and between their own OMU male and AMB males. In addition to the social status and competitiveness of adult males, female mate choice may play a major role in the usurpation of OMU males by AMB males ( Qi et al, 2009 ; Fang et al, 2018 ). Moreover, previous field observations have found that females usually initiate extra-pair copulations when their OMU males are not present.…”
Section: Introductionmentioning
confidence: 99%
“…The R. roxellana social structure thus provides adult females with opportunities to exhibit mate choice between their own OMU male and the other adult males within the breeding band, and between their own OMU male and AMB males. In addition to the social status and competitiveness of adult males, female mate choice may play a major role in the usurpation of OMU males by AMB males ( Qi et al, 2009 ; Fang et al, 2018 ). Moreover, previous field observations have found that females usually initiate extra-pair copulations when their OMU males are not present.…”
Section: Introductionmentioning
confidence: 99%
“…Takeovers of OMUs by other males also occur frequently. Nevertheless, female preferences appear to strongly influence whether the resident male is replaced by another male ( Fang et al 2018 ) or whether the group becomes unstable and fissions ( Kirkpatrick and Grueter 2010) . Thus, OMU membership appears to be the outcome of a complicated process involving male–male competition, female preferences ( Zhang et al 2006 ; Qi et al 2009 ), and possibly female–female competition.…”
mentioning
confidence: 99%
“…Their resident males attempt to block AMU males from access to the females in their unit, but often fail to prevent extra-unit copulations. As such, females appear to be able to express their preferences for both social mates and extra-unit mates by directly choosing to mate with resident males, seeking extra-unit copulations, joining other OMUs, or by deserting new resident males that have recently taken over their OMU ( Fang et al 2018 ). However, it is unclear how much male age is associated with their preferences.…”
mentioning
confidence: 99%
“…By extending their stay in their natal group, young males would increase their opportunities to affiliate and initiate social bonding with young females in other units, and thus increase the likelihood of establishing their own breeding unit via female recruitment in the future. In golden snub-nosed monkeys, female choice plays an important role during the processes leading up to the usurpation of an OMU leader male by another male in both the wild and in captivity (Ren et al, 2007;Fang et al, 2018). In this study the male ST, who delayed dispersal, successfully became an OMU leader without first transferring to the AMB soon after his natal BZT-unit collapsed.…”
Section: Discussionmentioning
confidence: 69%